A comparison of elliptical zone and 3d scanning calculating methods of estimating swimmer's body segment volumes - Machtsiras, G.; Sanders, R. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In swimming, anthropometric data are combined with three-dimensional motion analysis techniques to compute the centre of mass (CM) location of the body segments and whole body (WBCM). Kinematics and kinetics of the body motion can then be derived. For this reason high accuracy is necessary to identify the location of the WBCM precisely. The `e-Zone` software developed by Deffeyes and Sanders (2005) is a modified version of the elliptical zone method (Jensen, 1978) enabling the identification of the location of the segment CMs and subsequently the WBCM. The body is divided into segments and each segment is modelled as a series of elliptical cylinders whose volume is computed and summed to make the volume of the whole body (WB). The aim of the current study is to assess the accuracy of the e-Zone software by comparing directly the volume of each body segment measured by 3D scanning. Method A national level swimmer volunteered to participate in the study. The volume of the head, neck, thorax, abdomen, right upper limb and right lower limb segment was measured when standing in the anatomical position with the use of the e-Zone software and also with the use of 3D body scanning techniques. Symmetry in the sagittal plane was assumed and only the right upper and lower limbs were measured in both cases. A front and side view photograph was taken simultaneously for the requirement of the e-Zone method and the radii of each elliptical cylinder was measured from the photographs with manual digitizing. The digitizing process was repeated five times to establish reliability. In parallel, a 3D laser scanner (Hamamatsu®) was employed to create an accurate 3D representation of the swimmer`s body. The model was then edited and segmented with the use of Rhinoceros® software whereas the segment volumes were measured with the use of the Magics® software. Results The volume of the WB was computed to be 74230.90 cm3 with the eZone method and 76613.90 cm3 with the 3D scanning technique. The head and neck volume was overvalued by 3.7% whereas the core, the right upper and lower limb were undervalued by 3%, 2.7% and 4.5% respectively. Discussion The findings of this study demonstrate that the volume of the full body was undervalued. These findings suggest that the estimates of segment mass and the location of the WBCM could have been affected. Further investigation of the accuracy of the e-Zone method with a greater number of participants and of both genders is necessary to draw a safe conclusion. Also, the effect of the WB volume measurement error in the location on the WBCM should be investigated.